Fingerprint wizards: the secrets of forensic science - Piper, Ross (Capstone Publishers Minnesota, 2008)
"An introduction to forensic science procedures including the examination of fingerprints, DNA, gunpowder, fibers, and handwriting found at a crime scene"--Provided by publisher